Acromegaly and pregnancy: a systematic review and meta-analysis - Bandeira, Diego Barata [UNESP] (2022)
Purpose: To evaluate the association between acromegaly and pregnancy in terms of disease activity, maternal and fetal outcomes. Methods: This systematic review was conducted according to the Joanna Briggs Institute methodology for systematic reviews of etiology and risk. We focused on observational studies that included pregnant women with acromegaly. The outcomes were acromegaly activity, preterm birth, gestational diabetes, hypertension, eclampsia/preeclampsia, miscarriage, perinatal mortality, low birthweight, small for gestational age, and congenital malformations. Embase, Medline, LILACS, and CENTRAL were our source databases. To perform proportional meta-analyses, we used Stata Statistical Software 17. Results: Nineteen studies were included encompassing a total of 273 pregnancies in 211 women with acromegaly. The overall frequency of control of acromegaly during pregnancy was 62%, and of tumor growth was 9%. No fetal or maternal deaths were reported. The overall frequency of worsening of previous diabetes or development of gestational diabetes was 9%, and of previous hypertension or preeclampsia/eclampsia was 6%. The overall frequency of premature labor was 9% [from 17 studies of 263 pregnancies; 95% confidence interval (CI), 5–13%]; of spontaneous miscarriage was 4% (from 19 studies of 273 pregnancies; 95% CI, 2–11%); of small for gestational age was 5% (from 15 studies of 216 newborns; 95% CI, 3–9%); and of congenital malformations was 1% (from 18 studies of 240 newborns; 95% CI, 0–7%). Conclusion: Pregnancy in women with acromegaly is frequently associated with disease control and is safe in relation to fetal and maternal outcomes, as in women without acromegaly.